Developing Effective Long-Haulage Infrastructure in Sweden through the Lens of TEN-T: Insights into stakeholder preferences for truck stop safety, security, service, and alternative fuels - Hedvall, Jakob; Linde, Albin (My University, 2025)
This thesis investigates how rest and refueling infrastructure for long-haul heavy goods vehicles (HGVs) in Sweden can be developed to better meet regulatory requirements and stakeholder needs, particularly in the context of the Trans-European Transport Network (TEN-T). The study applies a mixed-method approach combining a literature review, expert and haulage company interviews, and a driver survey. Key themes include safety and security, service availability, and the implementation of alternative fuels such as electricity and hydrogen. Using the Kano model and Multi-Criteria Decision Analysis (MCDA), the research identifies which resting area features add the most value to truck drivers. The findings reveal that basic hygiene and health services, and secure parking features are considered essential. These preferred features differ slightly from the required features that the EU has defined in their safe and secure certification requirements. Moreover, demographic factors such as gender, nationality, and exposure to crime, affect how features are perceived and prioritized. These preferences were compared with qualitative data from expert and haulage company interviews, and literature. Slight variations were found in what the qualitative and quantitative data suggests as important features. The report presents three development scenarios ranging from a core model focused on driver satisfaction to more advanced modules including alternative fuel infrastructure and a higher degree of safety and functionality. By comparing stakeholder preferences with EU certification criteria and funding opportunities, the study outlines practical and strategic recommendations for infrastructure investments. It concludes that aligning infrastructure development with user needs and funding eligibility is crucial to achieving both operational relevance and long-term sustainability in the Swedish transport sector.
Keywords: TEN-T; Long-Haulage Transport; Safe and Secure Parking; Service Design; Road Transport Infrastructure; Kano Model; Stakeholder Analysis